18F-Flurodeoxyglucose and 18F-Sodium Fluoride Positron Emission Tomography/Computed Tomography Imaging of Arterial and Cutaneous Alterations in Pseudoxanthoma Elasticum. (January 2018) - Mention, Pierre-Jean; Lacoeuille, Franck; Leftheriotis, Georges; Martin, Ludovic; Omarjee, Loukman
Abstract : Supplemental Digital Content is available in the text.